2016
DOI: 10.3390/technologies4030022
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Outcomes for Children with Cerebral Palsy Who Use Gait Trainers

Abstract: Gait trainers are walking devices that provide additional trunk and pelvic support. The primary population of children using gait trainers includes children with cerebral palsy (CP) functioning at Gross Motor Function Classification System (GMFCS) levels IV and V. A recent systematic review found that evidence supporting the effectiveness of gait trainer interventions for children was primarily descriptive and insufficient to draw firm conclusions. A major limitation identified was the lack of valid, sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 83 publications
1
8
0
Order By: Relevance
“…In children and youth with CP, controlled trials have largely focused on activity capacity motor outputs, such as improvements in walking speed ( 9 , 25 ) and endurance ( 29 ). However, reports in this study are consistent with previously reported uncontrolled trials and case series which provided early evidence of outcomes beyond walking speed and endurance which include improved confidence and mood ( 7 ), improved weight acceptance and transfers ( 30 ), reduced caregiver support, improved skills in gait trainers, and improved bowel function ( 31 ). In addition to this, parents provided the context of the perceived improvements that were meaningful to them.…”
Section: Discussionsupporting
confidence: 89%
“…In children and youth with CP, controlled trials have largely focused on activity capacity motor outputs, such as improvements in walking speed ( 9 , 25 ) and endurance ( 29 ). However, reports in this study are consistent with previously reported uncontrolled trials and case series which provided early evidence of outcomes beyond walking speed and endurance which include improved confidence and mood ( 7 ), improved weight acceptance and transfers ( 30 ), reduced caregiver support, improved skills in gait trainers, and improved bowel function ( 31 ). In addition to this, parents provided the context of the perceived improvements that were meaningful to them.…”
Section: Discussionsupporting
confidence: 89%
“…The fPRC conceptualises a health condition and the interplay of various constructs based on the WHO’s International Classification of Functioning, Disability and Health (ICF) 50. The GAS is valid and reliable,51 and has detected change across a variety of paediatric populations 52. The GAS produces a t-score for analysis, with a t-score of 50 or more indicating clinical meaningfulness 53.…”
Section: Methodsmentioning
confidence: 99%
“…Individually specific goals -GAS The GAS was used to enable individualized goal setting for activity and participation outcome measures with excellent measurement properties across all GMFCS levels. 19 Goals on the GAS were set on the basis of goals identified by parents on the Canadian Occupational Performance Measure (COPM). 20 Each GAS was individualized enabling more detail from the COPM to be objectively assessed and scored by the assessor who was blinded to group allocation.…”
Section: Primary Outcome Measuresmentioning
confidence: 99%
“…For children with CP that require gait trainers, there are limited motor-based outcome measures that have strong psychometric properties and this is an important area for future research. 19 The selection of the 10mWT is a limitation and though walking speed is associated with functional ability and quality of life in children with CP both with and without gait trainers, 25 there is inadequate data to support the psychometric properties of the 10mWT in children functioning in GMFCS levels IV and V. The 10mWT only provides an indication on walking speed leaving the descriptive aspects of the gait trainer unaccounted for. This includes changes in the degree of support, quality of steps, steering, and verbal prompting.…”
Section: Difference Within Groupsmentioning
confidence: 99%